Resposta :
Após anáslise da afirmações sobre as propriedades dos logarítmos temos:
F-F-V-V-V
[tex]I. log (A-B) = log A-log B \\\Afirmativa Falsa\\II. log (A + B) = log A + log B \\Afirmativa Falsa\\III. log A^3 = 3 log A \\Afirmativa correta\\IV. log A/B = log A-log B \\Afirmativa Correta\\V. log (A. B) = log A + logB\\Afirmativa correta\\[/tex]
Veja mais em:
https://brainly.com.br/tarefa/18519529
https://brainly.com.br/tarefa/20262203
![Ver imagem SOCRATESA](https://pt-static.z-dn.net/files/df2/a7cf63154284d26e5daed0d761417bc9.png)